Teoria dos estilos de aprendizagem para planejamento e desenvolvimento de disciplinas no Moodle - Alves, Francielle (2015)
This research is part of the Educational Technology Management Online Network of Educational Technology Master's Program in Network UFSM and left reflecting on learning styles, as well as the idea of identifying which resources and activities are being used by teachers / tutors in the Virtual Learning Environment - Moodle. In addition to identify the difficulties they encounter in their work in Moodle, in order to inform knowledge about the Theory of Learning Styles. In this sense, behind theoretical elements on Learning Styles, beyond research with distance tutors who work in the course of UFSM Pedagogy / UAB to prepare the final product. In the data analysis it was observed that if the teacher / tutor diversify the presentation of educational content and materials, as well as realizing the difficulties between teacher / tutor is possible to achieve more significant results. A document with guidance on the learning styles for planning and developing courses in Moodle as a final product of this research has been prepared. It adopted the qualitative research and grounded nature on case study methodology. The relevance of this work is found in the path taken in this project, since every step there was the importance of clarifying and broadening our knowledge of the theory of Learning Styles.